Studi Penentuan Tarif Buy the Service Transpakuan Koridor 6 Metode Ability to Pay dan Willingness to Pay - Ardila, Fitri Aning Ayu Dwi; Murtedjo, Tedy; Chayati, Nurul (Journal of Applied Civil Engineering and Infrastructure Technology, 2023)
Buskita Transpakuan is mass transportation in Bogor City which is increasingly in demand by the wider community. Based on this, a study on determining tariffs using the Ability to Pay and Willingness to Pay methods was carried out. This study aims to determine the applicable rates for Transpakuan BTS. This study uses a quantitative descriptive method, namely research that analyzes numerical data (numbers) and then analyzes it to conclude. The results showed (Ability to Pay) greater than Rp. 4180.00 from the WTP (Willingness to Pay) Rp. 4,000.00 occurs because users have higher paying abilities but satisfaction with the services used is still low so user willingness is relatively low, so service improvements are needed, and for the results the current decent tariff is Rp. 4,090.00 if rounded up to Rp. 4000.00. The service improvement priority desired by Buskita Transpakuan Corridor 6 passengers is the comfort aspect, followed by the safety aspect. The acquisition of headway values ​​on Mondays, Tuesdays, Thursdays, and Saturdays on 9 Buskita Transpakuan Corridor 6 Bogor City transportation routes that pass through the Parung Bison - Air Mancur route has met the indicator standards because the average headway value of 8.1 minutes, the ideal rating of 5-10 minutes. This was influenced by the level of transportation operations, the majority of which were still high.